Laparoscopic Common Bile Duct Exploration for Retrieval of Impacted Dormia Basket following Endoscopic Retrograde Cholangiopancreatography with Mechanical Failure: Case Report with Literature Review - J. W. O’Brien; R. Tyler; S. Shaukat; A. M. Harris (Case Reports in Surgery)
Dormia baskets are commonly used during endoscopic retrograde cholangiopancreatography (ERCP). One complication is basket retention, through impaction with a gallstone or wire fracture. We describe a case where the external handle of the basket snapped causing retained basket plus large gallstone impacted in the common bile duct (CBD). Following laparoscopic cholecystectomy, laparoscopic CBD exploration allowed direct stone fragmentation under vision with the choledochoscope. Fragments were removed using a choledochoscopic basket and Fogarty catheter, and the basket was withdrawn. Literature search identified 114 cases of retained baskets with management including shockwave lithotripsy (27%), papillary balloon dilatation (22%), open CBD exploration (11%), and one laparoscopic case.